Prefabricated Zirconia Crowns and Preformed Metal Crowns in the Treatment of Severely Childhood Caries and Anterior Crossbite in a Child with Autistic Spectrum Disorder - Shuman Deng; Qi Gao; Li Zhang; Jing Xie; Ying Chen; Xuezhen Peng (Case Reports in Dentistry)
Crowns have been recommended to treat decayed teeth and rebuild teeth function. The dental management of children with autism is a tremendous challenge for pediatric dentists due to the impaired behaviors and communication disorders. In this context, a 5-year-old boy with autism was treated to solve carious lesions under the assistance of general anesthesia. The posterior occlusal function was restored, and the crossbite existing in the primary anterior teeth was approached merely by NuSmile® zirconia crowns (ZCs) rather than orthodontic intervention. We conducted an 18-month period. Throughout the long-term follow-up, the boy’s masticatory efficiency was remarkably improved and the anterior teeth had transferred into the correct position with adequate overbite to maintain the new relationship, thus ameliorating the appearance of tissue on the labial surface and enhancing his quality of life and oral health.